Inventory Management and Financial Performance of Nepalese Public Enterprises - Risal, Nischal; Acharya, Sangita (Journal of Business and Social Sciences, 2021)
The objective of the research paper is to analyze the inventory management and the profitability of PE in Nepal. The descriptive and analytical research designs have been adopted in the study. The quantitative research approach has been used in the study. The population of the study is 37 public enterprises in Nepal. NFC, HPPC, and DDC are the samples taken based on purposive sampling method. The descriptive analysis, correlation analysis, and multiple regression analysis tools have been used in the study with seven years data from the years 2011AD to 2017AD. The variables used are CR, QR, CCC, ITR, ROA, ROE, OM, firm growth, and size of the firm. The results provide the negative and insignificant relationship between inventory turnover and liquidity ratios with profitability. The results concluded the negative and insignificant relationship with current assets, quick assets with profitability. CCC is found as insignificant positive relationship with profitability. Thus, the study concluded that PE in Nepal should manage their working capital efficiently to achieve the optimal profitability even though the study found no significant relationship of inventory management on the profitability of PEs in Nepal. The study highly recommend to not to ignore the inventory management by Nepalese public enterprises.